Social stratification as a catalyst for xenophobia in Kenneth Maswabi's poems - Abdullahi, Nafiu; Ali Termizi, Arbaayah; Kaur, Hardev; Muhammad Amin, Hasyimah (UKM Press, 2022)
This research aims to analyse selected poems from the anthology, Collection of Poems by Kenneth Maswabi (2020), that deal with social stratification as a source of xenophobia. Postcolonial theory is selected and adopted for the purpose of analysis of the texts under study. The purpose of applying postcolonial theory is to appropriately contextualize the text while analyzing it from a postcolonial standpoint. To address the impact of xenophobia and its link to social stratification, three poems were chosen, studied, and analysed. The study took into account South Africa's historical context and linked it to contemporary developments in the country. David Mário Matsinhe's concept of citizenship is adopted from postcolonial theory. Matsinhe's concept of citizenship has been chosen because he contends that the struggle for citizenship and survival in South Africa, as well as anti-immigrant sentiments, has revitalized group interactions in postcolonial Africa, often with fatal repercussions. Hence, the historical antecedents have sparked xenophobic assaults in South Africa since they refer to the country's colonial past. This demonstrates that during colonialism's repression, people learned to build resistance to any type of foreign incursion, particularly from African immigrants. As a result of these attitudes, a schism developed between citizens and immigrants. Based on the findings of the study, xenophobia caused social stratification, as proven by the analysis of the chosen poems.